(3GdeMGSHI GdVQjHjI Ydi GdQhGJH hGdGLhQ (B:s (3MGdGJ hJWHjbGJ YedjI eNJdaI (B/s - (3GdaQjLGJ, jGSQ UGdMs ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2007)
(3jMJhj gPG GdcJGH Ydi GdhMOGJ GdJGdjI (B: (3GdhMOI GdChdi hGdJj Je ajgG GdJQcjR Ydi GdCWGQ GdfXQj GdYGe ddfXGe GdVQjHj ehVMG fTCI GdVQjHI hGdJWQb Gdi eaghe GdJgQH GdVQjHj hGdJgQH GdCSJKeGQj CeG GdhMOI GdKGfjI aJe GdJQcjR ajgG Ydi WQb GdJbOjQ GdVQjHj hWQb GdJMUjd GdVQjHj CeG GdhMOI GdKGdKI eaghe GdCQHGM GdVQjHjI CVGaI Gdi Cge GdeaGgje GdeQJHWI HGdONd GVGaI Gdi MGdGJ YedjI hCSFdI aj fgGjI cd aUd(B.s
(3HjHdjhZQGajG U(B. 211s
Keywords: (3GdVQGFHs; (3eMGSHI VQjHjIs